Dampak Digitalisasi dalam Pembangunan: Strategi Meningkatkan Pendapatan Daerah di Kabupaten Tulang Bawang - Yuledi, Ferli (Tapis: Jurnal Penelitian Ilmiah, 2024)
Tulang Bawang Regency is a district located in Lampung Province, Indonesia. As a regional government unit, Tulang Bawang Regency faces various challenges in managing its regional finances. The financial performance of the Regional Revenue Center in Tulang Bawang Regency is very important because it will affect the district's ability to provide public services to its people. Good financial performance will help in financing development projects, infrastructure development, health services, education, and various other important sectors that are needed by local communities. The challenge faced by Tulang Bawang Regency is the complexity of planning, managing, and allocating regional financial resources, especially Regional Original Income which is the main source of regional income. Apart from that, strategic policies implemented by the regional government also have a very important role in determining the financial performance of Tulang Bawang Regency. The main objective of this research is to determine the influence of strategic policies and Regional Original Income on the financial performance of the Regional Revenue Center in Tulang Bawang Regency. With a better understanding of the factors that influence regional financial performance, the Tulang Bawang Regency government can plan more effective policies to improve community welfare and regional development.